The concept of self-directed piling rig / Nur Syaza Ismail and Noor Azam Yahaya - Ismail, Nur Syaza; Yahaya, Noor Azam (2019)
Piling has been around since the early start of the man-made construction. This paper contains the concept of self-directed piling rig. This is to tackle down problem faced by using the existing piling rig in the industry. The existing piling rig is unsafe and inadequate due to nature of it which are takes time to complete the piling from start to finish and the needs of labor to remain in the close distance to the heavy machine while piling. The purpose of this research is to analyze the existing piling rig and what improvement that can be done. The proposed concept for the innovation of the piling rig is by using radio control to mechanize the piling rig and using Global Positioning System (GPS) to ensure the accuracy of the piling point without having to do the positioning work manually. This study also examines the current technology used for the construction equipment. These innovations are to eliminate the problem faced in completing the piling stage of the construction.